The Paracetamol overdose and Sesame oil protective role against hepatotoxicity and some physiological parameters - Bulkasim M. Abdulnabi; Ahmed M. A. Hamad; Azhar Abdalgani Mohamed; Miftah Larbid Mohammed waheedah (African Journal of Advanced Pure and Applied Sciences, 2025)
The study dealt with the protective effects of sesame oil against paracetamol-induced toxicity in male rabbits. Paracetamol administration resulted in hepatotoxicity, evidenced by increased serum levels of bilirubin, ALT, AST, and LDH, alongside a depression in total protein and albumin. It also induced hematological disturbances, characterized by a significant decrease in red blood cells and hemoglobin and an increase in white blood cells. Co-treatment with sesame oil significantly mitigated these toxic effects, normalizing red blood cell and hemoglobin levels and markedly reducing the elevation in liver enzymes and bilirubin, although these levels of total protein remained significantly different from the control. The white blood cell count was also reduced but not fully normalized. The results demonstrate that sesame oil provides significant hepatoprotective and hematoprotective benefits against paracetamol toxicity.